Pyruvate as a Potential Beneficial Anion in Resuscitation Fluids - Zhou, Fang-Qiang (Frontiers in Medicine, 2022)
There have been ongoing debates about resuscitation fluids because each of the current fluids has its own disadvantages. The debates essentially reflect an embarrassing clinical status quo that all fluids are not quite ideal in most clinical settings. Therefore, a novel fluid that overcomes the limitations of most fluids is necessary for most patients, particularly diabetic and older patients. Pyruvate is a natural potent antioxidant/nitrosative and anti-inflammatory agent. Exogenous pyruvate as an alkalizer can increase cellular hypoxia and anoxia tolerance with the preservation of classic glycolytic pathways and the reactivation of pyruvate dehydrogenase activity to promote oxidative metabolism and reverse the Warburg effect, robustly preventing and treating hypoxic lactic acidosis, which is one of the fatal complications in critically ill patients. In animal studies and clinical reports, pyruvate has been shown to play a protective role in multi-organ functions, especially the heart, brain, kidney, and intestine, demonstrating a great potential to improve patient survival. Pyruvate-enriched fluids including crystalloids and colloids and oral rehydration solution (ORS) may be ideal due to the unique beneficial properties of pyruvate relative to anions in contemporary existing fluids, such as acetate, bicarbonate, chloride, citrate, lactate, and even malate. Preclinical studies have demonstrated that pyruvate-enriched saline is superior to 0.9% sodium chloride. Moreover, pyruvate-enriched Ringer’s solution is advantageous over lactated Ringer’s solution. Furthermore, pyruvate as a carrier in colloids, such as hydroxyethyl starch 130/0.4, is more beneficial than its commercial counterparts. Similarly, pyruvate-enriched ORS is more favorable than WHO-ORS in organ protection and shock resuscitation. It is critical that pay attention first to improving abnormal saline with pyruvate for ICU patients. Many clinical trials with a high dose of intravenous or oral pyruvate were conducted over the past half century, and results indicated its effectiveness and safety in humans. The long-term instability of pyruvate aqueous solutions and para-pyruvate cytotoxicity is not a barrier to the pharmaceutical manufacturing of pyruvate-enriched fluids for ICU patients. Clinical trials with sodium pyruvate-enriched solutions are urgently warranted.